Generation of scientific knowledge: dimensions of analysis for educational innovation in ecuadorian universities - Andino Sosa, Edgar Patricio; Garrido Arroyo, María del Carmen; Fernández Sánchez, María Rosa (IJERI: International Journal of Educational Research and Innovation, 2021)
Knowledge experiences a constant development that has accompanied the historical journey of man. The explanation about the nature of knowledge is manifested in the different philosophical and educational currents from ancient times to the present day. In each of the stages through which he has passed, he encountered a set of problems of various kinds, for which multiple solutions had to be generated to guarantee their existence. It is interesting to know the vision and interpretation of these currents, it will allow a better understanding of the current situation regarding the generation of knowledge. There are various institutions and organizations that, throughout history, have dealt with the generation of knowledge, universities are one of them; among its key functions are teaching and research. The study of Ecuadorian universities and, specifically, the UTE University, has made it possible to know its composition, analyze the legislation on which it is based for its organization and development of its functions, as well as identify various dimensions related to the generation of knowledge in the processes university academics. All of this has given us a complete vision of the institution of higher education in order to address the educational innovation processes that contribute to the generation of scientific knowledge and teaching.